Clinical effect of Kanpo treatment on glossodynia - HORI, Shinsuke; KUSUMOTO, Takashi; KANEDA, Noriko; MURAKAMI, Kenichiro; IIZUKA, Tadahiko; BESSHO, Kazuhisa; KOH, Saiseki (Japanese Journal of Oral and Maxillofacial Surgery, 1994)
The present study was conducted to evaluate the clinical usefulness of Sai-boku-to (Kanpo medicine) for the treatment of glossodynia. Oral administration of 7.5 g Sai-boku-to per day for one to two months was performed to treat glossodynia. Clinical examinations were carried out in order to evaluate subjective symptoms such as pain, heat sensation and unpleasent feelings. The success rate was 60% after one month and 82.4% after two months' administration. Mild side effects, recorded in 3 cases, disappeared without any treatment, and did not preclude the long-term use of Sai-boku-to. These results demonstrate that Sai-boku-to is a clinicaly useful drug for the treatment of glossodynia.